2019
DOI: 10.1002/ese3.501
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the factors influencing methane adsorption on illite

Abstract: The molecular simulation method was used to investigate the adsorption behaviors of methane on illite. The effects of several factors on methane adsorption, free gas amounts, and the proportions of absorbed gas in the illite nanopores, including the pore size, temperature, and water content, are discussed. The results obtained show that methane adsorption in illite nanopores is due mainly to van der Waals adsorption. With an increase in the pressure or of the pore size, the free gas amounts of methane increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The degree of hydrophilicity or lipophilicity depends on the oxygencontaining functional groups distributed on the surface of organic matter. According to the author's previous research results, 22,23,58,59 the competitive adsorption capacity of water molecules existing in quartz pores, illite pores, and organic matter pores is better than that of methane molecules, which can affect the methane adsorption capacity in nanoscale pores in shales. In organic matter pores, water molecules gather near oxygen-containing functional groups in a directional arrangement, but a certain number of methane molecules are still distributed near the pore wall.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of hydrophilicity or lipophilicity depends on the oxygencontaining functional groups distributed on the surface of organic matter. According to the author's previous research results, 22,23,58,59 the competitive adsorption capacity of water molecules existing in quartz pores, illite pores, and organic matter pores is better than that of methane molecules, which can affect the methane adsorption capacity in nanoscale pores in shales. In organic matter pores, water molecules gather near oxygen-containing functional groups in a directional arrangement, but a certain number of methane molecules are still distributed near the pore wall.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that H 2 O preferentially adsorbs and accumulates on the slit wall and kaolinite shows strong hydrophilicity. Due to the fact that water molecules are polar molecules, there are strong electrostatic forces and van der Waals forces between water molecules and the slit wall, and there are hydrogen bonds between water molecules [15][16][17]. With the increase in the number of water molecules, H 2 O will gradually appear in the middle of the slit and increase with the further increase in the number of H 2 O molecules.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…Li et al [16] suggested that stronger interactions between water molecules and the slit walls (electrostatic forces and van der Waals forces) would occupy more adsorption space leading to a significant decrease in the amount of CH 4 adsorbed in illite, montmorillonite and chlorite. Xiong et al [17] concluded that the electrostatic force between water molecules and the wall and the hydrogen bonding effect between water molecules make it easy for water molecules to accumulate on the surface of minerals to occupy the adsorption space, which is unfavorable for CH 4 adsorption. Huang et al [18,19] in their study found that the occupation of enterable pores by H 2 O in the form of clusters lead to a decrease in the adsorption capacity of CH 4 and CO 2 in casein.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 At the same time, X-ray diffraction (XRD) and total organic carbon (TOC) measurements show that illite, montmorillonite, and calcite are the major components of the clay types in the shale. 32,33 Therefore, based on the above research and the problems to be solved, this paper adopted the molecular simulation method to comparatively analyze the methane and carbon dioxide adsorption and diffusion performances in these three minerals and to explore the influences of different buried depths on their adsorption and diffusion performances.…”
Section: Introductionmentioning
confidence: 99%
“…Certain achievements have been attained regarding the mechanisms underlying the adsorption and diffusion behaviors of methane; , however, most studies focus on the adsorption and diffusion behaviors of methane in single minerals. In actual practice, shale is usually jointly constituted by multiple minerals with significant differences in the sizes of pores that can store gas, which means that the adsorption capacities of minerals for methane are different. , At the same time, X-ray diffraction (XRD) and total organic carbon (TOC) measurements show that illite, montmorillonite, and calcite are the major components of the clay types in the shale. , Therefore, based on the above research and the problems to be solved, this paper adopted the molecular simulation method to comparatively analyze the methane and carbon dioxide adsorption and diffusion performances in these three minerals and to explore the influences of different buried depths on their adsorption and diffusion performances.…”
Section: Introductionmentioning
confidence: 99%